2022
DOI: 10.2147/idr.s376443
|View full text |Cite
|
Sign up to set email alerts
|

Liver Abscess Combined with Endogenous Endophthalmitis Caused by Genotype ST25 Serotype K2 Hypervirulent Klebsiella pneumoniae: A Case Report

Abstract: At present, invasive syndrome caused by hypervirulent Klebsiella pneumoniae (HvKp) is a widespread concern, and HvKp strains of different genotypes have been isolated. Here, we report a case of community-acquired liver abscess and endogenous endophthalmitis caused by a genotype ST25 serotype K2 (ST25-K2) HvKp strain in China. A 51-year-old man with diabetes was transferred to our hospital from a local community hospital with persistent fever for > 20 days and blurred vision in his left e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…PLA caused by multidrug-resistant hvKp has rarely been reported (Table 4). [19][20][21][22][23][24][25][26] The strain in our case showed a trend of multidrug resistance. There needs to be awareness of infection caused by hypervirulent strains with drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…PLA caused by multidrug-resistant hvKp has rarely been reported (Table 4). [19][20][21][22][23][24][25][26] The strain in our case showed a trend of multidrug resistance. There needs to be awareness of infection caused by hypervirulent strains with drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Kp is a threat to public health and can cause a range of severe infections, such as pneumonia, BSI, meningitis, urinary tract infection, and bacterial abscesses (Dong et al, 2019;Lai and Yu, 2021), which can result in high mortality rates of hospitalized patients (Shapaka et al, 2023). Based on virulence factors, Kp is commonly classified as classic or hypervirulent (Liu and Guo, 2018;Zhu et al, 2021;Lin et al, 2022). Routine culture methods for detection of Kp BSIs have relatively low positivity rates (10% to 30%) and are time-consuming (Zhou et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…LABACER 01 and LABACER 27, hypermucoviscous carbapenem resistant K. pneumoniae ST25 strains, were isolated at the “Angel Cruz Padilla” hospital (San Miguel de Tucuman, Tucuman, Argentina). ST25 K. pneumoniae strains were identified by MALDI-TOF (matrix-assisted laser desorption/ionization) (Microflex LT; Bruker Daltonik GmbH, Bremen, Germany) and kept in the Culture Collection of the Certified Bacteriology Laboratory (LABACER, National University of Tucuman, Tucuman, Argentina) [ 4 , 5 , 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, an increase in the prevalence of hypermucoviscous carbapenem-resistant K. pneumoniae of the sequence type (ST) 25 was detected in patients hospitalized in Northwest Argentina. This hypermucoviscous phenotype has been associated with hypervirulent strains, leading this bacterium to cause different infectious diseases including liver abscesses, meningitis, endophthalmitis, prostate abscesses and respiratory infections [ 4 , 5 ]. In this sense, our previous studies have shown that K. pneumoniae carbapenemase-2 (KPC-2)-producing ST25 strains are endemic in hospitals in the province of Tucuman (Argentina) and are associated with respiratory and systemic infections [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%